(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the role of the state in the economy from an institutional perspective, focusing on how formal and informal institutions shape economic outcomes. It examines the state’s involvement in creating and enforcing legal frameworks, protecting property rights, reducing transaction costs, and promoting economic development. Additionally, the paper discusses how institutional changes influence the state’s role in addressing market failures, fostering economic stability, and ensuring equitable growth. Through an analysis of historical and contemporary cases, the article highlights the dynamic relationship between state institutions and economic performance, emphasizing the importance of institutional reforms in modern economies.